2015
DOI: 10.1126/scisignal.aac8321
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the signaling pathways that mediate cancer in PTEN and LKB1 double-knockout mice

Abstract: Double knockout of PTEN and LKB1-genes encoding phosphatase and tensin homolog and liver kinase B1, respectively-leads to the spontaneous development of cancer in mice. PTEN converts phosphatidylinositol (3,4,5)-trisphosphate (PIP3) to phosphatidylinositol (4,5)-bisphosphate (PIP2), whereas LKB1 activates the 5' adenosine monophosphate-activated protein kinase (AMPK). The kinase AKT and the kinase complex mTORC1 may play key roles in carcinogenesis and are components of signaling pathways that also contain PTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 17 publications
0
26
1
Order By: Relevance
“…Although encouraging progress in diagnosis and cancer therapy has been achieved in the past decade, the 5-year overall survival rate is less than 10% in advanced disease and chemotherapy treatment remains essential for these patients. The activation of survival signaling pathways such as EGFR, PI3K/Akt, MAPK and STAT3 plays key roles in colon cancer initiation, development, progression and drug resistance, and therapies targeting those signaling axes are beneficial 36. The chemotherapy drugs such as 5-fluorouracil, oxaliplatin (OXA), irinotecan, cetuximab and bevacizumab are the first-line options for treatment of metastatic colorectal cancer 79.…”
Section: Introductionmentioning
confidence: 99%
“…Although encouraging progress in diagnosis and cancer therapy has been achieved in the past decade, the 5-year overall survival rate is less than 10% in advanced disease and chemotherapy treatment remains essential for these patients. The activation of survival signaling pathways such as EGFR, PI3K/Akt, MAPK and STAT3 plays key roles in colon cancer initiation, development, progression and drug resistance, and therapies targeting those signaling axes are beneficial 36. The chemotherapy drugs such as 5-fluorouracil, oxaliplatin (OXA), irinotecan, cetuximab and bevacizumab are the first-line options for treatment of metastatic colorectal cancer 79.…”
Section: Introductionmentioning
confidence: 99%
“…After delivery of chemotherapeutics, liposomes can be used to interfere directly (or through the delivery of compounds that interfere with protumorigenic pathways) with, for instance, block expression of AkT and PD-L1 molecules, which have been linked with tumor progression. 61,62 Sun et al 63 showed successful siRNA and doxorubicin co-delivery to cells in vitro. With these niosomes, siRNA delivery resulted in sensitization of tumor cells for doxorubicin.…”
mentioning
confidence: 99%
“…Indeed, the pro-apoptotic effects of citropten are well documented in the literature. [26][27][28][29][30][31][32] In the cited works, the antiproliferative effects of the plant molecule on tumor cells due to the alteration of specific signal transduction pathways, such as those of mitogenactivated protein kinase (MAPK) and PI3K/Akt (important in cancer survival and proliferation), suggested the use of citropten as a potential chemotherapy drug. On the other hand, the quantification of C levels per cell ( Figure 2B), which rapidly increased up to reach a sort of plateau at 48-72 hours of treatment, corroborated the finding that the plant molecules were accumulated in the cell cytoplasm but not metabolized during the time.…”
mentioning
confidence: 99%